O2A.2 Pesticides and respiratory health; the GB based pipah study. (April 2019) - Fishwick, David; Harding, Anne-Helen; Fox, David; Yiqun, Chen; Pearce, Neil; Frost, Gillian
Abstract : We administered a cross sectional respiratory questionnaire in January to 4814 PIPAH (Prospective Investigation of Pesticide Applicators' Health) participants. Of the 2562 respondents (53% response) with a median age of 60.2 years, 97.4% were male and 34.1% ever smoked. The prevalence of ever doctor diagnosed conditions was 11.4% for asthma, 1.29% for COPD, 0.9% for chronic bronchitis and 0.4% for farmer's lung. Self-reported symptoms, however, were more prevalent. Nasal allergies were reported by 21.4%, coughing in winter (possibly signifying chronic bronchitis) by 13.7%, chest tightness or difficulty in breathing by 12.9% and trouble in breathing by 9%. The majority (n=1806, 86%) had mixed, loaded handled or applied pesticides in the last 12 months, in a range of work areas. For those respondents actively using pesticides, the association between respiratory health and pesticide use was investigated using logistic regression. Doctor diagnosed; none of the doctor diagnosed conditions were statistically associated with (binary) pesticide use in the last 12 months. Doctor diagnosed asthma was only associated with age (OR 0.987, p=0.024) and ever smoking (OR 1.47, p=0.004). Self-reported; self-reported nasal allergies (OR=1.81), chest tightness (OR=2.18) and trouble breathing (OR=2.68) were associated with 'golf courses, bowling greens, sports grounds' work, cough (OR=1.91) with forestry and cough (OR=1.4) and wheeze (OR=1.31) with grain store work. After adjustment for age, self-reported nasal allergy was significantly inversely associated with pesticide use (OR 0.72, p=0.03), although no significant associations with pesticide use were identified for other self-reported symptoms. This study has identified low levels of doctor diagnosed ill health in this group, in contrast to more prevalent self-reported symptoms; suggesting the possibility of under-diagnosis of respiratory ill health. Forestry and grass-exposed areas were associated with nasal allergies and cough. Pesticide use specifically was only associated with nasal allergies.